Implementation of the Smoke-Free Policy in the Tourist Destination Area of Lake Toba, Toba Samosir Regency, Indonesia - Novi Susanti; Desty Adinda; Abdillah Ahsan; Putra Apriadi Siregar; Dina Ayu Wardani; Nada Nurjanah Afrillia; Prima Yanti Siregar; Tri Bayu Purnama (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The prevalence of smoking in Indonesia remains alarmingly high, with early initiation among children and adolescents contributing to a significant burden of smoking-attributable diseases and escalating national healthcare costs. Despite the implementation of a Smoke-Free Policy (SFP) in Toba Samosir Regency, particularly in the Lake Toba tourist area, compliance remains low, undermining efforts to create a healthy, smoke-free environment for both residents and visitors.Objectives: Beautiful scenery of Lake Toba is not followed by clean and healthy air; this is because there are still many smokers found, the smell of cigarette smoke and cigarette butts in the priority tourist attractions of Lake Toba, Toba Samosir Regency. This study aims to determine the implementation of the Toba Samosir Regents smoke-free policy on the Regional Regulation No. 55 of 2018 Toba Samosir in the priority tourist destination area of Lake Toba, Toba Samosir Regency. This study uses a cross-sectional design. The object of this research is the priority tourist destination area of Lake Toba, Toba Samosir Regency Random cluster sampling was used to choose samples from the population. These samples included 100 tourist facilities on Lake Toba, 100 tourists on Lake Toba tourist facilities, and 100 tourist managers. JASP version 16 was used to analyze the data. The results of this study show that tourist facilities still need to follow the smoke-free policy (SFP) more (21%). Beaches and waterfalls have the lowest rates of smoke-free policy (SFP) compliance for tourist facilities (0%), restaurants and cafes (8.3%), hills and mountains (20%), monuments (22.2%), hotels (38.1%), and markets and souvenir places (60%). Most smoke-free policy (SFP) violations are no sign (68%), smoking (42%), ashtrays (38%), and cigarette butts (32%). Overall compliance was low in Toba Samosir Regency due to many challenges. This information provides lessons regarding tobacco control policy in underdeveloped areas far from the central government. Keyword: Compliance, Smoke, Smoke-free policy, Tourism facilities.